PENGARUH ION Cu2+ , Zn2+ , Cd2+ dan Cr3+ TERHADAP PEYERAPAN LOGAM Pb2+ MENGGUNAKAN KULIT PISANG KEPOK (Musa Paradisiaca L) SEBAGAI BIOSORBEN - Delvia Yollanda, Edi Nasra, Desy Kurnia Indang Dewata, Umar Kalmar Nizar (Menara Ilmu, 2019)
The research has done on the effect of Cu2+, Zn2+, Cd2+ and Cr3+ ions on the absorption ofmetal Pb2+ by using kepok banana peel as biosorbent. The parameters are determined theeffect of concentrations of ions Cu2+, Zn2+, Cd2+ and Cr3+ which can affect the absorptionprocess of metal Pb2+. With variatious concentration of disrupting ions 40 ppm, 80 ppm,160 ppm, 240 ppm, 400 ppm. The result of research has showed the increasing theconcentration of ions Cu2+ and Zn2+ and reduce the absorption of metal Pb2+ with apercentage of reduction in each absorption of 3.126% and 7.274%. Addition of ions Cd2+and Cr3+ to the absorption of metal Pb2+ tends to disrupt at a concentration of 80 ppm, 160ppm and 240 ppm with a percentage of decrease in absorption of 0.344% and 1.594%. Thevariation of concentration in increasing of irritation ions decreases the absorptioncapacity of metal Pb2+ in the biosorbent of kepok banana peel, which is influenced by thelevel of ionic radius.Keywords – biosorption, metal Pb, Kepok Banana Peel